How does community education encourage sustainable development? A comprehensive strategy strengthens the role of community facilitators - Sucipto, Sucipto; Nasih, Ahmad Munjin; Raharjo, Kukuh Miroso; Fatihin, Muhammad Khoirul (Jurnal Cakrawala Pendidikan, 2024)
The primary objective of this study was to enhance the proficiency of professional community assistants to promote the achievement of Sustainable Development Goals (SDGs) within rural communities in Indonesia. Utilizing qualitative methodologies encompassing observational techniques, interviews, document analysis, and focus group discussions (FGDs), the research formulated a comprehensive approach. The suggested methodology promotes self-directed learning, active involvement in professional communities, participation in training initiatives, structured communication with supervisors, attentiveness to community development matters, cooperation with local authorities, and the development of comprehensive planning materials. These tactics enable community facilitators to enhance the alignment of their duties with the objectives of the SDGs. Nevertheless, the study admits several inherent limits that arise from the intricate nature of varied community contexts, restrictions on resources, and the varying levels of engagement from local leadership. To tackle these challenges, it is imperative for future research to prioritize long-term impact assessments, thoroughly examine contextual factors that influence the effectiveness of strategies, and endeavor to quantify the influence of these strategies on the achievement of the SDGs. By doing so, research can establish a more robust basis for policy recommendations and initiatives aimed at community development.